2016
DOI: 10.1158/1078-0432.ccr-14-3296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis and Targeted Therapies for Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (iCCA) is a molecularly heterogeneous hepatobiliary neoplasm with poor prognosis and limited therapeutic options. The incidence of this neoplasm is growing globally. One third of iCCA tumors are amenable to surgical resection, but most cases are diagnosed at advanced stages with chemotherapy as the only established standard of practice. No molecular therapies are currently available for the treatment of this neoplasm. The poor understanding of the biology of iCCA and the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 82 publications
2
176
0
2
Order By: Relevance
“…Targeting single pathways either as monotherapy or in combination with chemotherapy has shown varying degrees of improvements in response rates, but these have not translated to clinically significant increases in PFS or OS. Currently, some clinical trials are using a multi-target approach by using multikinase inhibitors or a combinatorial approach with multiple agents aimed at different pathways (12,72). Results from studies using multikinase inhibitors regorafenib and pazopanib are anxiously awaited.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Targeting single pathways either as monotherapy or in combination with chemotherapy has shown varying degrees of improvements in response rates, but these have not translated to clinically significant increases in PFS or OS. Currently, some clinical trials are using a multi-target approach by using multikinase inhibitors or a combinatorial approach with multiple agents aimed at different pathways (12,72). Results from studies using multikinase inhibitors regorafenib and pazopanib are anxiously awaited.…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…In addition, the clinical data of CCAs are usually collected over many years with a limited number of patients for the rarity of this disease, which inevitably lead to bias for the variability of diagnosis and treatment strategy. All these factors contribute to the difficulty of making comparisons between series and preclude clinical practice guidelines in establishing a "standard of care" for patients with advanced CCAs [15]. More confirmed evidences and treatment strategies are eagerly awaited for CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, no mutations were found in IDH1/2 or FGFR2 gene fusions, which has been described as important potential targets in iCCA. [20,21] A limited number of studies have investigated differences within the extrahepatic group and the conclusions that currently can be drawn are limited. One example is the differential expression of cell cycle related proteins between pCCA and dCCA, where some studies has shown that dCCA expressed a pattern more closely resembling pancreatic ductal adenocarcinoma (PDAC).…”
Section: Cholangiocarcinoma -Current Classification and Challenges Tomentioning
confidence: 99%
“…This development has been ongoing, primarily in iCCA, in which several studies have investigated the molecular pathogenesis and identified potential biomarkers, as well as goals for targeted therapy. [20] The number of studies characterising eCCA is significantly lower and there is a need of elucidating the molecular pathogenesis, as well as identifying unique biomarkers of pCCA and dCCA, respectively. This division will be necessary, not only because there are underlying differences in tumour biology, but also to deal with unique clinical problems in pCCA and dCCA.…”
Section: Cholangiocarcinoma -Current Classification and Challenges Tomentioning
confidence: 99%